2021
DOI: 10.1371/journal.pone.0255375
|View full text |Cite
|
Sign up to set email alerts
|

Survival analysis in lung cancer patients with interstitial lung disease

Abstract: Objective Lung cancer patients with interstitial lung disease (ILD) are prone for higher morbidity and mortality and their treatment is challenging. The purpose of this study is to investigate whether the survival of lung cancer patients is affected by the presence of ILD documented on CT. Materials and methods 146 patients with ILD at initial chest CT were retrospectively included in the study. 146 lung cancer controls without ILD were selected. Chest CTs were evaluated for the presence of pulmonary fibrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…Our model demonstrated that patients with ILD; lymphocyte counts ≤0.8 × 10 9 /L; docetaxel, vinorelbine, and S‐1 chemotherapy regimens; and PaO 2 s ≤80 mmHg have worse OS. We also showed that patients with NSCLC and ILD have significantly shorter PFS and OS times than do those with NSCLC without ILD, similar to previous reports 15,19,20 . Alomaish et al 15 found that the 5‐year survival rates for patients with lung cancer with and without ILD were 41% and 48%, respectively, and that ILD comorbidity increased the risk of death by 1.522 times.…”
Section: Discussionsupporting
confidence: 90%
“…Our model demonstrated that patients with ILD; lymphocyte counts ≤0.8 × 10 9 /L; docetaxel, vinorelbine, and S‐1 chemotherapy regimens; and PaO 2 s ≤80 mmHg have worse OS. We also showed that patients with NSCLC and ILD have significantly shorter PFS and OS times than do those with NSCLC without ILD, similar to previous reports 15,19,20 . Alomaish et al 15 found that the 5‐year survival rates for patients with lung cancer with and without ILD were 41% and 48%, respectively, and that ILD comorbidity increased the risk of death by 1.522 times.…”
Section: Discussionsupporting
confidence: 90%
“…Besides the decrease in FVC and carbon monoxide diffusion capacity (DLCO) in patients who developed both IPF and LC, another aspect to investigate are the histopathological findings. Previous studies have shown that squamous cell carcinoma is the most common histologic type encountered in IPF [51][52][53][54][55][56][57][58][59][60][61][62]. This aspect would highlight the importance of considering older patients with a diagnosis of IPF who have a long and heavy history of smoking and whose median FVC and DLCO are slightly lower than normal [63].…”
Section: Diagnostic Approaches For Idiopathic Pulmonary Fibrosis and Lung Cancermentioning
confidence: 96%
“…Indeed, it has been thought that patients with a very rapid decrease in FVC and consequent IPF progression are more sensitive to lung cancer development; however, further studies will need to be conducted to clarify the common factors between cancer and IPF. A recent study demonstrated a median time from IPF to lung cancer of 38 months [53], although Tomassetti et al [52] found the time to be around 30 months. Besides the decrease in FVC and carbon monoxide diffusion capacity (DLCO) in patients who developed both IPF and LC, another aspect to investigate are the histopathological findings.…”
Section: Diagnostic Approaches For Idiopathic Pulmonary Fibrosis and Lung Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to progressive decline in lung function and AE-ILD, patients with IPF are at risk for pulmonary hypertension, venous thromboembolism, and lung cancer (6)(7)(8). Patients with coexistent ILD and lung cancer have a worse survival than patients with lung cancer alone (9).…”
mentioning
confidence: 99%